Sonographically Diagnosed Vault Hematomas Following Vaginal Hysterectomy and Its Correlation with Postoperative Morbidity - Cem Dane; Banu Dane; Ahmet Cetin; Murat Yayla (Hindawi Limited, 2007)
Objective. Our aim is to investigate sonographically detectable vault hematomas after vaginal hysterectomy and its relation to postoperative morbidity. Methods. We studied a group of 103 women who had undergone vaginal hysterectomy for benign causes apart from uterovaginal prolapse. Transabdominal ultrasound examinations were carried out 24 to 72 hours after surgery to assess the presence of vault hematomas. Ultrasound findings were correlated with clinical data and postoperative morbidity. Results. The incidence of vault hematoma was found 19.4% in present study. In these patients, 40% (8/20) had fever while only 2.4% (2/83) of cases without vault hematoma suffered from fever. Out of all women having vault hematoma, 70% (14/20) had small-sized hematoma and 30% (6/20) had large-sized hematoma. Fifty percent of patients (3/6) with large-sized hematoma, as compared to only 35% (5/14) with small-sized hematoma, suffered from febrile morbidity. Large-sized hematomas drained by vaginally, while all small-sized pelvic hematomas managed by watchful expectancy successfully. The significant difference was found mean hemoglobin drop and postoperative stay in the hematoma group or without hematoma group. Conclusion. Sonographic detection of vaginal vault fluid collection is common after hysterectomy, but such a finding rarely indicates additional treatment. Though febrile morbidity was more in cases with vault hematoma, the number of such patients was too small to be significant. Vaginal ultrasound examination should not be performed routinely after hysterectomy.